Konvergensi antara Liberalisme dan Kolektivisme sebagai Dasar Etika Politik di Indonesia - Dwi Siswanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
The polical ethics in matters peratining to the state possess a strategic menaning as a reference understanding of the development of human nature. Beside that, the political ethics has a function as a tool of analysis for question and clarification toward a political legitimate which responbility, rationality, objectivity, and argumentatively; not depend on emotion and apriori.Indonesia's political ethics based on Pancasila seem a convergence between liberalism and collectivism, although The Pancasila values rooted in Indonesian real life. Anthropological of The Indonesia's political ethics based on the human nature are